Effect of Post-Weaning Concentrate Feeding Prior to Forage Finishing on Intramuscular Fat Deposition - Duckett, Susan (2024)
The objectives of this study were to examine the effects of feeding high-concentrate diets post-weaning (PW) prior to forage finishing on (1) changes in ultrasound intramuscular fat deposition and lipogenic/lipolytic gene expression during the post-weaning phase and (2) carcass characteristics and fatty acid composition after forage finishing to 487 kg. Steers were randomly assigned to one of four treatments (PW0, PW40, PW80, and PW120) at weaning to examine the time of high-concentrate feeding prior to forage finishing. The ultrasound intramuscular fat content was greater (p < 0.05) for PW120 compared to those for PW0, PW40, or PW80 at the end of the post-weaning phase. Feeding high concentrates (PW120) up-regulated (p < 0.01) the mRNA expression of fatty acid transporters and lipogenic genes and down-regulated lipolytic genes in the LM compared to PW0. Carcasses from PW120 were graded 83% Choice (p = 0.025), whereas carcasses from other post-weaning treatments (PW0, 40, or 80) were graded 25, 36, and 54% Choice, respectively, at the final harvest. The total fatty acid content of the muscle at slaughter was greater (p = 0.0004) for PW120 than PW0, PW40, and PW80. Feeding high-concentrate diets to steers post-weaning for 120 day enhanced early intramuscular fat deposition without causing major changes to the fatty acid composition of the longissimus muscle after forage finishing.